Rationally Managed Pastures Stock More Carbon than No-Tillage Fields - Seó, Hizumi L. S.; Machado Filho, Luiz C. P.; Brugnara, Daniel (Frontiers in Environmental Science, 2017)
A significant share of Greenhouse Gases (GHG) produced from agriculture comes from cattle farming. The reduction in GHG emissions from ruminants fed with grains has led some researchers to recommend such a diet as a means of mitigating emissions in the sector. A more accurate balance of emissions, however, must include the carbon (C) stocked by feed crops. Within the grain production system, no-tillage (NT) cultivation systems have a greater capacity to increase and store soil organic carbon (SOC). Within grazing management systems, the rotation used in Voisin's Rational Grazing (VRG) allows the accumulation of SOC through root growth. The objective of this study was to assess the C stock of pasture under VRG and compare soil C stock between VRG pasture and fields under no-tillage management, in two seasons over a period of 1 year. The study included five dairy farms in Santa Catarina State, Brazil. In each property, we collected soil to quantify SOC from VRG pasture and NT fields, in summer and winter. In the pasture, to determine the total stock, we also collected samples from the aerial parts of plants and the roots. Further, we estimated how efficient would be producing milk from those pastures or from those crops. The VRG pasture showed a greater capacity to stock C in the soil than the no-tillage fields (VRG = 115.0 Mg C ha−1; NT = 92.5 Mg C ha−1; p < 0.00009), with the greatest difference at a depth of 0–10 cm (VRG = 41 Mg C ha−1; NT = 32 Mg C ha−1; p < 0.00008). In VRG, 95% of C was in the soil, 1% in the aerial part of plants, and 4% in the roots. On pasture was produced 0.15 kg of milk.kg−1 of C stored, and on NT system 0.13 kg of milk.kg−1 of C stored. In this study, we conclude that independent of season, the soil in well managed pastures had a greater stock of C, produced more milk and produced more milk.kg−1 of stored C than fields under NT management. Therefore, when comparing GHG emissions of ruminants with different diets, we must also quantify the SOC resulting from distinct feed production systems.